1995
DOI: 10.1074/jbc.270.3.1015
|View full text |Cite
|
Sign up to set email alerts
|

Diphtheria Toxin Binds to the Epidermal Growth Factor (EGF)-like Domain of Human Heparin-binding EGF-like Growth Factor/Diphtheria Toxin Receptor and Inhibits Specifically Its Mitogenic Activity

Abstract: The membrane anchored form of human heparin-binding epidermal growth factor-like growth factor (HB-EGF) acts as the diphtheria toxin (DT) receptor. Transfection of human HB-EGF cDNA into mouse LC cells, L cells stably expressing DRAP27, conferred sensitivity to DT, but transfection of mouse HB-EGF cDNA did not. To define the essential regions of HB-EGF that serve as the functional DT receptor, we examined the sensitivity to DT and DT binding of cells expressing several human/mouse HB-EGF chimeras. It was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
236
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 281 publications
(245 citation statements)
references
References 32 publications
8
236
0
1
Order By: Relevance
“…Despite the fact that mice lack the required receptors for DTx binding, which significantly reduces the immunogenicity of CRM 197 in this model (13,23), we have shown that topical application of CRM 197 , without additional stabilization or formulation, is highly immunogenic for boosting diphtheria immunity in mice after parenteral priming with a conventional toxoid vaccine. Although initial neutralizing antibody responses were significantly enhanced in the presence of a mucosal adjuvant (LTR72), longer-term immunity induced by TCI using CRM 197 alone was comparable to immunity induced by TCI with adjuvant and to boosting with a conventional toxoid vaccine given by the classical parenteral route.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that mice lack the required receptors for DTx binding, which significantly reduces the immunogenicity of CRM 197 in this model (13,23), we have shown that topical application of CRM 197 , without additional stabilization or formulation, is highly immunogenic for boosting diphtheria immunity in mice after parenteral priming with a conventional toxoid vaccine. Although initial neutralizing antibody responses were significantly enhanced in the presence of a mucosal adjuvant (LTR72), longer-term immunity induced by TCI using CRM 197 alone was comparable to immunity induced by TCI with adjuvant and to boosting with a conventional toxoid vaccine given by the classical parenteral route.…”
Section: Discussionmentioning
confidence: 99%
“…This concentration (1.7 nM) is close to the concentration required for half-saturation of DT binding to human pro-HB-EGF (18,37). Nonspecific binding of 125 I-DT was assessed in the presence of 10 g/ml unlabeled DT.…”
Section: Methodsmentioning
confidence: 99%
“…DT Binding Assay-HB-EGF has been shown to act as a diphtheria toxin receptor (DTR) and binds to DT through its EGF-like domain (37). Previously, we reported that pro-HB-EGF associates with cell surface HSPGs, which increases its binding affinity for DT (32).…”
Section: Mutant Forms Of Hb-egf Lacking the Heparin-binding Domain-mentioning
confidence: 99%
“…Extracellular processing of the EGFR ligand, proheparin-binding epidermal growth factor (pro-HB-EGF) has been primarily implicated in EGFR activation by GPCRs (Prenzel et al, 1999). A mutated form of diphtheria toxin, CRM197, has been shown to bind specifically to HB-EGF and inhibit its mitogenic activity (Mitamura et al, 1995). Prenzel et al reported that CRM197 pretreatment could completely inhibit EGFR activation induced by GPCRs in COS-7 cells (Prenzel et al, 1999).…”
Section: Tgf-a Mediates Grp-induced Egfr Activationmentioning
confidence: 99%